Promoting preschoolers’ academic and social development with effective assessment practices - Devadason, Edward; Yee, Felicity Lee Wai; Teng, Cynthia Yeo Wee; Hussin, Farahimah; Paramasivam, Anusia (Edelweiss Applied Science and Technology, 2025)
The early childhood years are critical for establishing the groundwork for future academic and social success. This study explores the role of effective assessment practices in fostering preschoolers’ development in these areas. By examining contemporary assessment methodologies, the research offers teachers practical insights for enhancing early childhood education. Assessment practices extend beyond simply measuring academic progress; they are essential in shaping educational experiences tailored to the unique developmental needs of young children. This study highlights formative assessments, which are dynamic and ongoing, providing immediate feedback for customizing educational interventions. These include observational techniques, developmental checklists, and play-based assessments, offering a comprehensive view of a child’s growth. Observational methods allow teachers to document children’s interactions, behaviors, and skills in natural settings, while developmental checklists serve as benchmarks to identify areas needing support. Play-based assessments engage children in activities that reveal cognitive, social, and emotional strengths. A key focus is on culturally responsive assessments, crucial in diverse educational settings. These ensure tools and methods are relevant and fair, accurately reflecting each child’s abilities and respecting varied backgrounds. The findings reveal that effective assessment practices not only prepare children for academic challenges but also enhance social competence, including communication, empathy, cooperation, and emotional regulation. The research underscores the importance of involving parents in the assessment process, fostering strong teacher-parent partnerships that support comprehensive child development. Ultimately, effective assessment practices lay the foundation for personalized education, respecting each child’s individuality and cultural heritage, and preparing them for long-term success in school and life.